Transport demand of modes not covered in international transport statistics. Annex 5. ECF report on cycling. - Schollaert, U.; Coppieters, Marie Caroline; Flaxen, David; Bergerhoff, Joachim (My University, 1997)
The study gathered information on cycle use for the years 1970, 1975, 1980, 1985, 1990, 1994 and 1995 in the 15 member states of the European Union. Thereby it focuses on the mileage done by bicycle, data gained through statistical material or estimates from regional travel surveys.
Keywords: Individualverkehr; Fahrrad; Statistik; Fahrradbenutzung; Modal Split